Antidotes Against Methanol Poisoning: A Review - Pohanka, Miroslav (Mini-reviews in medicinal chemistry, 2019)
Methanol is the simplest alcohol. Compared to ethanol that is fully detoxified by metabolism. Methanol gets activated in toxic products by the enzymes, alcohol dehydrogenase and aldehyde dehydrogenase. Paradoxically, the same enzymes convert ethanol to harmless acetic acid. This review is focused on a discussion and overview of the literature devoted to methanol toxicology and antidotal therapy. Regarding the antidotal therapy, three main approaches are presented in the text: 1) ethanol as a competitive inhibitor in alcohol dehydrogenase; 2) use of drugs like fomepizole inhibiting alcohol dehydrogenase; 3) tetrahydrofolic acid and its analogues reacting with the formate as a final product of methanol metabolism. All the types of antidotal therapies are described and how they protect from toxic sequelae of methanol is explained.
Keywords: Alcohol Dehydrogenase; Molecular Structure; inhibitory enzymů; methanol; alkoholdehydrogenasa; Humans; lidé; Antidotes; Enzyme Inhibitors; antidota; molekulární struktura; Methanol